Relationship Between the Different Aspects Related to Coffee Quality and Their Volatile Compounds - Toledo, Paulo R.A.B. [UNESP]; Pezza, Leonardo [UNESP]; Pezza, Helena R. [UNESP]; Toci, Aline T. (My University, 2016)
This paper provides, for the first time, an overview of different aspects related to the quality of coffee beans and their volatile fractions: species/cultivars, geographic origins, bean defects, and types of beverages, processing, roasting, and storage. In other words, it concerns the complex relation between the quality of coffee seeds and their volatile components. It is an overview of 48 articles and considering 6 different aspects related to the quality of coffee and its aromatic fraction. The greatest numbers of published papers concerned “species and cultivars” and “defective seeds,” both with 11 articles cited, followed by “storage” with 10 articles. Many aspects still require greater clarification, including the effects of geographical origin, processing, and roasting. Other issues that are better understood include the effects of species type, defective seeds, and storage conditions. Another topic that has received very little attention is the question of the existence of many different coffee cultivars within each species, which we believe should be further investigated, given that this can significantly affect the quality of the final beverage. Meanwhile, with the growing technological development in the areas of science and agriculture, there are many other aspects to be studied (or revisited), and the field of the aromatic quality of coffee provides ample opportunity for scientific investigation.
Keywords: coffee aroma; coffee quality; odorants compounds; volatile compounds; volatile markers